Simulation and Experiment of a Kind of Thin-Walled Tube Crushing Member Used for Antiimpact Column - Cheng‐long Wang; Yifang Chen; QingLiang Zeng; Guoming Liu (Shock and Vibration)
In order to solve the problem of poor antiimpact ability of hydraulic support under rock bursting, a kind of thin-walled cylinder crushing component used in the composite spiral antiimpact device was developed, and different structural models were proposed and simulated. On this basis, the model was verified by experiments. The results show that the arrangement of the hollow structure can restrain the ring mode deformation and Euler instability of the tube member in the crushing yield and can carry out the buckling deformation according to the expected crushing force during the compression deformation process and effectively reduce the initial peak force. The arrangement of guide grooves can make the buckling deformation more stable and regular, which can effectively reduce the initial peak force and elastic displacement. With the smaller wall thickness and the smaller wall thickness of the induced groove, the effective deformation yield stroke of the crushing member increases, and the initial peak force, total energy absorption, average reaction force, and elastic displacement decrease. The simulation results are consistent with the experimental results which will be used in the future works.